Supporting nurse practitioner education: Preceptorship recruitment and retention - Eric Staples; Esther Sangster-Gormley (Elsevier, 2018)
Objectives: Clinical experience is an essential component of nurse practitioner (NP) education that relies heavily on preceptors. Recruitment and retention of preceptors is challenging due to many variables that can affect NP education and practice. We surveyed Canadian NP programs to understand their preceptorship structures, how they support preceptorship, and to identify gaps and challenges to recruitment and retention of preceptors. Methods: An 18-item survey, developed by the NP Education Interest Group, was distributed to 24 universities across 10 Canadian provinces. Construct validity and reliability was assessed by experienced NPs and NP faculty. Data were analyzed using relative frequency statistics and thematic analysis. Participants consisted of administrative staff and/or faculty designated as responsible for recruitment and retention of NP preceptors. Results: Seventeen returned surveys were analyzed and demonstrated more similarities than differences across Canada's NP programs, particularly related to barriers affecting recruitment and retention of preceptors. The findings identified NP programs have too many students for the number of available clinical sites/preceptors, resulting in overutilization, burnout, or refusal to take students. Competition with other health disciplines for clinical placements was identified as a challenge to placements. Respondents commented they lack time to recruit, provide follow-up, offer support, or seek preceptors' feedback due to competing work demands. They identified the need for standardized funding for preceptor remuneration and recognition across the country. Conclusion: The findings suggest the need for exploring a wider intraprofessional collaboration among graduate NP programs/faculty, clinical placement sites, and NPs to facilitate the recruitment and retention of preceptors.